Rủi ro địa chính trị và thị trường tài chính Việt Nam - Ngô Thái, Hưng; Nguyễn Thanh, Hùng; Lê Thành , Đặng; Nguyễn Thành, Đức (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2024)
This study aims to analyze the price spillover effects and examine correlation between Geopolitical Risk (GPR) and financial markets in Vietnam during the period 2018–2023, covering the US – China trade war, the COVID-19 pandemic, and the Russia – Ukraine crisis. By doing so, the authors employ the spillover index proposed by Diebold and Yilmaz (2012) and the Cross-Quantilogram developed by Linton and Wang (2007). Empirical results illustrate that the price spillover effects between GPR and Vietnam financial markets have a high level of 31.4%, which implies that there is a significant connectedness between these time series. In addition, the impact of GPR on financial markets is both positive and negative in the short term as well as gradually weaker in the medium run. These results have crucial implications for investors, portfolio managers and policymakers.